2009
DOI: 10.1111/j.1469-8986.2008.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

The speeding of voluntary reaction by a warning signal

Abstract: Warning signals can shorten reaction time (RT) via either a top-down mechanism, temporal attention, or a bottom-up one, phasic arousal. The goal of this review article is to identify the locus at which these processes influence RT. Electrophysiological and behavioral evidence indicate that the chronometric locus for both modulatory effects lies mainly within a narrow window at the center of the stimulus-response interval. This interval presumably encompasses late perceptual, response selection, and early motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 68 publications
5
70
1
7
Order By: Relevance
“…F(6, 126) = 1.174, p = .324. The reduced reaction times at the earliest TMS delays are likely due to intersensory facilitation (Nickerson, 1974) or increased arousal from the auditory stimulation associated with the TMS (Bertelson & Tisseyre, 1969;Hackley, 2009). Such reaction time changes have been observed in previous TMS studies (e.g., Sawaki, Okita, Fujiwara, & Mizuno, 1999).…”
Section: Reaction Timementioning
confidence: 97%
“…F(6, 126) = 1.174, p = .324. The reduced reaction times at the earliest TMS delays are likely due to intersensory facilitation (Nickerson, 1974) or increased arousal from the auditory stimulation associated with the TMS (Bertelson & Tisseyre, 1969;Hackley, 2009). Such reaction time changes have been observed in previous TMS studies (e.g., Sawaki, Okita, Fujiwara, & Mizuno, 1999).…”
Section: Reaction Timementioning
confidence: 97%
“…Other studies have located the effects of temporal expectancy in nonmotor aspects of cognitive processes, such as selection of the response category (Bausenhart, Rolke, Hackley, & Ulrich, 2006;Fischer, Plessow, & Kiesel, 2010;Hackley, 2009;Hackley & Valle-Inclán, 1998Los & Schut, 2008) or perception of target stimuli. With regard to the impact of expectancy on perception, Lange, Rösler, and Röder (2003) showed that EEG markers for perceptual attention were increased at the attended FP, relative to the unattended FP, when participants voluntarily scheduled their auditory attention to one of two FPs, in order to detect loudness-deviant tones (see also Lange & Heil, 2008;Lange, Krämer, & Röder, 2006).…”
Section: General Nonmotor Expectancymentioning
confidence: 99%
“…This improvement appears to arise at multiple levels, including the motor system (Burle, Tandonnet, & Hasbroucq, 2010;Sanders, 1998), response selection mechanisms (Hackley, 2009;Los & Schut, 2008), and perception (Bausenhart, Rolke, & Ulrich, 2008;Correa et al, 2005;Rolke & Hofmann, 2007). A foreperiod arises in most conventional AB experiments because all trials contain two targets that are presented with equal frequency at each potential lag.…”
mentioning
confidence: 99%